(untitled) (Global Journal of Medical Research, 2019)
Phenolic and Polyphenolic are important compounds from the class of phytomedicine and are widely distributed in the plant kingdom. Over the years, an increasing amount of interest has been vastly drawn into the plant polyphenolic mainly because these compounds have shown tremendous efficacy in the treatment of oxidative stress-related diseases such as cancer. Currently, much medical investigations are conducted on plant phenolic for improving their identification and development for better therapeutic efficacy in the fight against different types of cancers. We aim to update and provide an extensive overview of the mechanism of action and the role of phenolic compounds in the treatment of tumor. The various databases used to conduct the literature survey are (Pub Med Central, Scopus, Research Gate, EMBASE, Google Scholar, Science Direct, Sci ELO, PLoS (Public Library of Science). In the first stage it includes different types of cancers and their biomarkers. In second stage, different phenolic compounds in plants and their role in the cancer treatment. Finally, to find out the mechanism of action and clinical status of phenolic compounds against different biomarkers and the mechanism of action of phenolic and polyphenolic compounds against cancer and its biomarkers with their antioxidant activity.